Giant Encephalocoele: A Rare Case Report and Review of Literature - Naik, Vikas (Asian J Neurosurg, 2019)
Giant encephalocoeles are rare entities with only one case series and few case reports reported in medical literature. Encephalocoeles, which reach a size larger than the head size, are be called Giant encephalocoeles. We report a case of a 6 month old child who had giant encephalocoele with delayed motor milestones in the form of inability to hold neck. Anesthetic implications include difficulty in securing air way due without undue pressure on the sac. She underwent VP shunt followed by excision of the encephalocele sac. Patient is doing well at 1 year of follow up. Preoperative neurological status and amount of brain tissue herniating into the sac are the most important factors determining the long term prognosis.